Intimate Partner Violence During COVID-19 Restrictions: A Study of 30 Countries From the I-SHARE Consortium - Campbell, Linda Frye (Journal of interpersonal violence, 2023)
Intimate partner violence (IPV) causes substantial physical and psychological trauma. Restrictions introduced in response to the COVID-19 pandemic, including lockdowns and movement restrictions, may exacerbate IPV risk and reduce access to IPV support services. This cross-sectional study examines IPV during COVID-19 restrictions in 30 countries from the International Sexual HeAlth and REproductive Health (I-SHARE) study conducted from July 20th, 2020, to February, 15th, 2021. IPV was a primary outcome measure adapted from a World Health Organization multicountry survey. Mixed-effects modeling was used to determine IPV correlates among participants stratified by cohabitation status. The sample included 23,067 participants from 30 countries. A total of 1,070/15,336 (7.0%) participants stated that they experienced IPV during COVID-19 restrictions. A total of 1,486/15,336 (9.2%) participants stated that they had experienced either physical or sexual partner violence before the restrictions, which then decreased to 1,070 (7.0%) after the restrictions. In general, identifying as a sexual minority and experiencing greater economic vulnerability were associated with higher odds of experiencing IPV during COVID-19 restrictions, which were accentuated among participants who were living with their partners. Greater stringency of COVID-19 restrictions and living in urban or semi-urban areas were associated with lower odds of experiencing IPV in some settings. The I-SHARE data suggest a substantial burden of IPV during COVID-19 restrictions. However, the restrictions were correlated with reduced IPV in some settings. There is a need for investing in specific support systems for survivors of IPV during the implementation of restrictions designed to contain infectious disease outbreaks.